Diabetic Neuropathic Arthropathy of the Knee: Two Case Reports and a Review of the Literature - Amit Patel; Aaron K. Saini; Michael E. Edmonds; Venu Kavarthapu (Case Reports in Orthopedics)
Diabetic neuroarthropathy of the knee or Charcot knee (CK) is a lesser-known complication of diabetes mellitus, with a limited number of case reports and small case series published in the literature. The majority of these reports describe the complexities and challenges that arise in these patients undergoing knee arthroplasty procedures. We present two cases of CK, including a rare case of concurrent bilateral disease, and also a review of the current literature.